The Relationship between Psychological Well-Being and Motivation for Achievement in Bakrie Center Foundation Internship Students in Banten Province - Harvi Wahyu Putriadi; Zamralita Zamralita (Jurnal Indonesia Sosial Sains, 2024)
Internships aim to enrich students' knowledge and experience through direct fieldwork. Psychological well-being relates to fulfilling and realizing fundamental human qualities by actualizing one's potential. Therefore, students with high psychological well-being are expected to have better achievement motivation. This study aims to determine if there is a relationship between psychological well-being and achievement motivation among Bakrie Center Foundation interns in Banten Province. The scales used are the Psychological Well-Being Scale (PSWB) and the Achievement Motivation Scale adapted from Julianti (2022), based on McClelland's aspects. This quantitative research uses a correlational design, with a sample of 47 interns. Pearson correlation analysis yielded a Pearson correlation (r) value of 0.234 with a significance level (p) of 0.109 (p< 0.05), indicating no relationship between psychological well-being and achievement motivation among Bakrie Center Foundation interns in Banten. Overall categorization data showed that the interns had high psychological well-being but low achievement motivation.